Loyalitas dan Kepuasan Pelanggan Kapal pada Perusahaan Peti Kemas di Indonesia - Ulfa Soraya Batubara; Prasadja Ricardianto; Yosi Pahala; Johny Malisan; Imam Sonny (Institut Transportasi dan Logistik Trisakti, 2022)
Some problems were found such as the changing of export shipment booking system from manual process to online process that created an impact on customers’ perceived adjustments. In this study, there was problem with the Electronic Customer Relationship Management website based system in the implementation process. The purpose of the study is to find out the contribution of Electronic Customer Relationship Management and service quality to customers’ loyalty mediated by customers’ satisfaction, directly and indirectly, in container companies in Indonesia . The data analysis method used Path Analysis and Sobel Test. The sample were 103 respondents taken from PT. White Star Cruise shipping company’s customers. The data collection technique was using online questionnaires (google form). The results of the study show that the customers’ loyalty variable with the lowest average score of 3.75 can be improved by convincing customers that the service provided by PT. Bintang Putih Shipping Company is much better and can be guaranteed even though the rate offered is more expensive. Moreover, the customers’ satisfaction variable with the lowest average score of 3.85 can be increased by adjusting the rate received by the customers with the service obtained such as the on time arrival of goods at the destination port.